Prophetic Business Orientation in Corporate Law Efforts to Incorporate Aspects of Divinity and Justice in Business Law - Ida Ayu Sadnyini; I Gede Agus Kurniawan (Rechtsidee: Law Journal, 2023)
This article explores the integration of prophetic business orientation, which combines religious and ethical values into corporate law, in the context of globalized modern economics. It employs a normative research methodology and legislative approach, analyzing the incorporation of values like transparency, ethics, and religious principles in Indonesian corporate law. The study reveals challenges related to legal uncertainty, corruption, unequal access to justice, and gender inequality in the workplace. Legal reforms and improved law enforcement are vital to promote ethical values and justice in contemporary business practices.